Effect of vitamin D3 on the immunomodulation of head kidney after Edwardsiella ictaluri challenge in yellow catfish (Pelteobagrus fulvidraco). Issue 99 (April 2020) - Cheng, Ke; Tang, Qin; Huang, Yanqing; Liu, Xiaoling; Karrow, Niel A.; Wang, Chunfang
Abstract: Edwardsiella ictaluri ( E. ictaluri ) causes severe infections in yellow catfish ( Pelteobagrus fulvidraco ), which leads to a massive loss in the aquaculture industry especially in catfish commercial production. Previous studies have confirmed that vitamin D3 is essential in immune regulation in mammals. Based on next-generation sequencing, this study explored the immunomodulatory effects of dietary vitamin D3 on the head kidney of yellow catfish after E. ictaluri challenge. Current results showed that increasing the content of dietary vitamin D3 within the experimental concentration range (1120IU/kg-16600IU/kg) could reduce the mortality of the yellow catfish after E. ictaluri challenge. Results of the next-generation sequencing showed that dietary vitamin D3 regulates the immune mechanism of the head kidney mainly through three pathways i.e. negative regulation of interferon-β production, negative regulation of interleukin-6 production and neutrophil chemotaxis. Proteins HSPA8, MAP4K4 and MRC1 may be involved in vitamin D3 -mediated immunoregulation in the head kidney. qPCR results showed that increasing the content of dietary vitamin D3 can improve the immune function of the yellow catfish by down-regulating ifn-β and pro-inflammatory factors tnf-α, il1-β, il-6, il-8 and up-regulating the anti-inflammatory factor il-10 . The above results indicated that dietary addition of vitamin D3 regulated the immune response in head kidney of yellow catfish and helped the fish to resist the negative effects of infection by E. ictaluri in a dose-dependent manner. Graphical abstract: Image 1 Highlights: VD3 decreased the mortality of yellow catfish infected by E.ictaluri . VD3 affected IFN-β and IL-6 production and neutrophil chemotaxis in head kidney. VD3 down regulated ifn-β, tnf-α, il1-β, il-6, il-8 and up regulated il-10 . Proteins HSPA8, MAP4K4 and MRC1 were identified among different VD3 treatments.